Interventions that improve maternity care for immigrant women in the UK: protocol for a narrative synthesis systematic review - Higginbottom, Gina M.A.; Evans, Catrin; Morgan, Myfanwy; Bharj, Kuldip Kaur; Eldridge, Jeanette; Hussain, Basharat (BMJ Publishing Group, 2017)
Introduction: A quarter of all births in the UK are to mothers born outside the UK. There is also evidence that immigrant women have higher maternal and infant death rates and of inequalities in the provision and uptake of maternity services/birth centres. The topic is of great significance to the National Health Service (NHS) because of directives that address inequalities and the changing patterns of migration to the UK. Our main question for the systematic review is “what interventions exist that are specifically focused on improving maternity care for immigrant women in the UK”? The primary objective of this synthesis is to generate new interpretations of research evidence. Secondly, the synthesis will provide substantive base to guide developments and implementation of maternity services/birth centres which are acceptable and effective for immigrant women in the UK. Methods and analysis: We are using a narrative synthesis (NS) approach to identify, assess scientific quality and rigour, and synthesise empirical data focused on access and interventions that enhance quality of maternity care/birth centres for the UK immigrant women. The inclusion criteria include: publication date 1990 to present, English language, empirical research and findings are focused on women who live in the United Kingdom, participants of the study are immigrant women, is related to maternity care/birth centres access or interventions or experiences of maternity. In order to ensure the robustness of the NS, the methodological quality of key evidence will be appraised using the Center for Evidence Based Management tools and review confidence with CERQual. Two reviewers will independently screen studies, extract relevant evidence. We will synthesise evidence studying relationships between included studies using a range of tools. Dissemination: Dissemination plan include: an e-workshop for policy makers, collaborative practitioner workshops, YouTube video and APP, scientific papers and conference presentations.